Transition metal heterogeneous heterojunction catalyst and preparation method and application thereof

By constructing a Co-CoO-C/Mo2N heterojunction on a Mo2N catalyst and performing thermochemical treatment, the problems of weak water dissociation ability and hydrogen adsorption of the Mo2N catalyst were solved, achieving highly efficient electrocatalytic hydrogen evolution performance, which is suitable for the field of electrocatalysis.

CN119265615APending Publication Date: 2025-01-07GUIZHOU WUJIANG HYDROPOWER DEV +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411327586.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing Mo2N catalysts exhibit weak water dissociation ability and strong H* adsorption in alkaline electrolytes, resulting in low electrocatalytic hydrogen evolution efficiency. Current modification methods suffer from high catalyst overpotential and low hydrogen evolution efficiency.

Method used

By constructing a CoMoO4 precursor and forming a multiphase heterojunction with carbon cloth, and then performing thermochemical treatment and heteroatom doping, a Co-CoO-C/Mo2N structure is formed, optimizing the electronic structure and active sites.

Benefits of technology

It significantly improves the electrocatalytic hydrogen evolution performance of the catalyst, exhibits excellent electrocatalytic activity, and its performance is close to that of Pt/C catalysts, making it suitable for large-scale preparation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005055848580000011
    Figure HDA0005055848580000011
  • Figure HDA0005055848580000012
    Figure HDA0005055848580000012
  • Figure HDA0005055848580000013
    Figure HDA0005055848580000013
Patent Text Reader

Abstract

The invention provides a transition metal heterogeneous heterojunction catalyst and a preparation method and application thereof. The method comprises the following steps: 1) providing a CoMoO4 precursor loaded on carbon cloth; and 2) placing the CoMoO4 precursor loaded on the carbon cloth in a reaction atmosphere by taking carbonitride which is easy to decompose by heating as a reaction source, carrying out heat treatment, and then cooling to room temperature to obtain the transition metal heterogeneous heterojunction catalyst. The catalyst constructs a heterogeneous heterojunction with nano metal / oxide and is doped with heteroatoms, so that the electronic structure of the catalyst is optimized, the number of active sites is remarkably increased, the problems that Mo2N has weak water dissociation capacity and improper hydrogen adsorption are effectively solved, and the catalyst shows excellent electro-catalytic hydrogen evolution performance; the preparation method is simple, raw materials are simple and easy to obtain, energy consumption is low, and batch preparation is facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of functional material preparation, and in particular relates to a transition metal multiphase heterojunction catalyst and a preparation method and application thereof. Background Art

[0002] Hydrogen has high energy density and environmentally friendly characteristics, and is a green and clean energy that can replace traditional fossil fuels. Compared with several other strategies for producing green hydrogen, water electrolysis is considered to be an efficient and green method for producing hydrogen. However, electrocatalytic hydrogen evolution has a high overpotential, resulting in high energy consumption and low efficiency. The overpotential of the hydrogen evolution reaction can be reduced by using suitable catalysts, and precious metal catalysts can reduce the activation energy of water decomposition and improve the efficiency of the hydrogen evolution reaction, but their high cost and limited availability hinder their widespread application.

[0003] Mo2N is considered to be the most promising non-precious metal catalyst due to its high conductivity, platinum-like electronic structure and easy preparation. However, due to the weak water dissociation ability and strong H* adsorption of Mo2N in alkaline electrolyte, its intrinsic catalytic activity is low, which directly affects its electrocatalytic hydrogen evolution efficiency. Modification of Mo2N by efficient and reasonable construction of highly active heterogeneous interfaces and introduction of heteroatom doping is of great significance to promote the practical application of Mo2N catalysts in electrocatalysis. Cobalt-based materials are the most commonly used electrocatalysts in alkaline electrolyzers. The addition of cobalt can optimize the hydrogen adsorption on the surface of Mo2N and promote water decomposition, so that Mo2N has excellent electrocatalytic hydrogen evolution activity. CN202210969308.1 uses an electrodeposition method to prepare a precursor, and then uses a chemical vapor deposition method to phosphate the precursor to obtain a Co / NiCoP / CC heterojunction catalyst; but the catalytic hydrogen evolution yield of the obtained product is low. CN202310635258.8 discloses a double heterojunction catalyst for electrocatalytic hydrogen evolution reaction and a preparation method thereof, wherein a mixture of WS2 nanosheets coated with cobalt-nitrogen co-doped carbon framework material and sulfur element is calcined under oxygen-free conditions to obtain a WS2 / Co9S8 / Co4S3 double heterojunction material, which has an excellent electronic structure that can optimize the conductivity of WS2, and the collective synergistic effect of the double heterojunction can reduce the hydrogen adsorption energy and water decomposition barrier; however, the double heterojunction catalyst prepared by this method has a high overpotential and also has problems such as low hydrogen evolution efficiency. Therefore, further exploring the preparation of high-stability multi-component electrocatalysts by simple, efficient and controllable methods has important research and application significance. Summary of the invention

[0004] The main purpose of the present invention is to provide a transition metal multiphase heterojunction catalyst and a preparation method and application thereof in view of the problems and shortcomings of the prior art. By constructing a multiphase heterojunction with nanometal / oxide and performing heteroatom doping, the electronic structure thereof is optimized, the number of active sites is significantly increased, and the problems of weak water dissociation ability and inappropriate hydrogen adsorption of Mo2N are effectively solved, and excellent electrocatalytic hydrogen evolution performance is exhibited. The preparation method involved is relatively simple, the raw materials are simple and easy to obtain, the energy consumption is low, and it is conducive to batch preparation.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] A method for preparing a transition metal multiphase heterojunction catalyst comprises the following steps:

[0007] 1) providing a CoMoO4 precursor loaded on a carbon cloth;

[0008] 2) Using a carbonitride that is easily decomposed by heat as a reaction source, placing the CoMoO4 precursor supported on the carbon cloth in a reaction atmosphere, performing a thermochemical treatment, and then cooling to room temperature to obtain the transition metal multiphase heterojunction catalyst.

[0009] The above scheme further includes a step of performing a secondary annealing on the product obtained in step 2) in an argon atmosphere after step 2).

[0010] In the above scheme, the temperature of the secondary annealing is 500-700° C., and the holding time is 1-6 hours.

[0011] Preferably, the annealing temperature of the secondary annealing is 500-600° C., and the holding time is 1.5-2 hours.

[0012] In the above scheme, the carbonitride is one of urea, cyanamide, dicyanamide or melamine, and the added amount of the hydrocarbon is 0.5-1g.

[0013] Preferably, the carbonitride is urea.

[0014] In the above scheme, the reaction gas in step 2) is a mixed atmosphere of hydrogen and argon, wherein the volume concentration of H2 is 5-10 vol%, and the flow rate is 30-300 sccm.

[0015] Preferably, the flow rate is 200 sccm.

[0016] In the above scheme, the temperature of the heat treatment in step 2) is 500-800° C., and the time of the heat treatment is 1-6 hours.

[0017] Preferably, the heat treatment temperature in step 2) is 500-600° C., and the heat treatment time is 2-4 hours.

[0018] In the above scheme, the CoMoO4 precursor has the morphology of nanorods, with a diameter of 100 to 800 nm and a length of 5 to 10 μm.

[0019] In the above scheme, the CoMoO4 nanorod precursor loaded on the carbon cloth is prepared by dissolving Na2MoO4·2H2O and Co(NO3)2·6H2O in water, immersing the carbon cloth in water, performing a hydrothermal reaction, and washing the carbon cloth to obtain the CoMoO4 precursor loaded on the carbon cloth.

[0020] In the above scheme, the hydrothermal reaction temperature is 60-120° C., and the insulation time is 1 to 6 hours.

[0021] The transition metal multiphase heterojunction catalyst obtained by the preparation method.

[0022] The application of the transition metal multiphase heterojunction catalyst in the field of electrocatalytic hydrogen evolution.

[0023] The reaction principle of the present invention is:

[0024] Take urea as an example of a reaction source. During the heat treatment process, urea first decomposes to release reducing ammonia and hydrocarbons. Under the combined action of the ammonia atmosphere and hydrocarbons, the CoMoO4 precursor undergoes a phase separation reaction and transforms into carbon-doped CoO-Mo2N (CoO-C / Mo2N). During the above reaction, an argon-hydrogen atmosphere is introduced into the reaction space at the same time. Due to the difference in thermal stability of different metal compounds, part of the CoO is reduced to metallic Co, while Mo2N remains unchanged, eventually forming a Co-CoO-C / Mo2N multiphase heterogeneous structure.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1) Using transition metals as raw materials, a method for uniformly growing transition metal materials with multiphase heterogeneous interfaces on the surface of carbon cloth has been developed. The raw materials used in this method are cheap and easily available, the products are controllable, and it is conducive to large-scale preparation.

[0027] 2) The transition metal material prepared by this method has abundant electrocatalytic hydrogen evolution active sites, which are comparable to Pt / C catalysts, and has very broad application prospects in the field of electrocatalysis.

[0028] 3) The transition metal material obtained by the present invention has strong adhesion and good electrocatalytic stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the preparation process of Co-CoO-C / Mo2N of the present invention;

[0030] Figure 2 The scanning electron microscope image and X-ray diffraction pattern of the CoMoO4 nanorod array of the present invention;

[0031] Figure 3 The X-ray diffraction pattern of Co-CoO-C / Mo2N obtained in the embodiment of the present invention;

[0032] Figure 4 The following are scanning electron microscope images of the Co-CoO-C / Mo2N catalysts obtained in the examples of the present invention. (a) is a scanning electron microscope image of the Co-CoO-C / Mo2N obtained in Example 1; (b) is a scanning electron microscope image of the Co-CoO-C / Mo2N obtained in Example 2; (c) is a scanning electron microscope image of the Co-CoO-C / Mo2N obtained in Example 3;

[0033] Figure 5 TEM image and element distribution diagram of Co-CoO-C / Mo2N obtained in Example 1 of the present invention.

[0034] (a) TEM image; (bc) HR-TEM image; (d) EDS element mapping diagram of Co, Mo, O, N, and C;

[0035] Figure 6 The X-ray photoelectron spectrum of Co-CoO-C / Mo2N obtained in Example 1 of the present invention. Among them, (a) is the Mo 3d fine spectrum; (b) is the Co 2p fine spectrum; (c) is the C1s fine spectrum; (d) is the N1s fine spectrum;

[0036] Figure 7 This is the hydrogen evolution polarization curve of Co-CoO-C / Mo2N obtained in the embodiment of the present invention under 1.0M KOH conditions;

[0037] Figure 8 This is the Tafel slope diagram of Co-CoO-C / Mo2N obtained in the embodiment of the present invention under 1.0M KOH conditions;

[0038] Fig. 9 This is the X-ray diffraction pattern of the product obtained in Comparative Example 1 of the present invention;

[0039] Fig.10 This is the X-ray diffraction pattern of the product obtained in Comparative Example 2 of the present invention;

[0040] Fig.11 The X-ray diffraction pattern of the product obtained in Comparative Example 3 of the present invention;

[0041] Fig.12 This is the X-ray diffraction pattern of the product obtained in Comparative Example 4 of the present invention;

[0042] Fig.13 The X-ray photoelectron spectrum of the product obtained in Comparative Example 4 of the present invention is shown in Figure 4. (a) is the Mo 3d fine spectrum; (b) is the C1s fine spectrum. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0044] In the following examples, the raw material used is CoMoO4 nanorod array, and the specific preparation method includes the following steps: 0.605g Na2MoO4·2H2O and 0.725g Co(NO3)2·6H2O are dissolved in 30mL distilled water and dispersed evenly by ultrasonication. A piece of carbon cloth (3cm×4cm) is immersed in the solution for 10min, then taken out and dried in an oven at 60°C. Next, the carbon cloth seeded with CoMoO4 seeds is annealed in air at 300°C for 10 minutes to promote the formation of nanoparticles. The treated carbon cloth is sealed in a stainless steel polytetrafluoroethylene autoclave (50mL) containing the same solution as above and heated in an oven at 90°C for 2 hours. After cooling to room temperature, the sample is taken out, washed several times with distilled water and ethanol, and then dried in an oven at 60°C for 12 hours to obtain the CoMoO4 nanorod precursor; its XRD and SEM images are shown in FIG. Figure 2 , where the length is about 8 μm and the surface is smooth.

[0045] Example 1

[0046] A transition metal multiphase heterojunction catalyst, the preparation process diagram of which is shown in Figure 1 , specifically including the following steps:

[0047] 1) Place the prepared CoMoO4 precursor in a crucible in a tube furnace, place 0.5g of urea in the crucible and place it upstream of the quartz tube, with the distance between the urea and the sample being about 6cm. Pass 7% H2 / Ar (the volume ratio of hydrogen is 7%) at a flow rate of 200sccm at 5℃min -1 The tube furnace was heated to 500 °C at a heating rate of for 2 h and then cooled to room temperature;

[0048] 2) Subsequently, the temperature of the tube furnace was raised to 600° C., and the atmosphere was changed to argon, and the sample was kept warm in the argon environment for another 2 hours to improve the crystallinity of the sample. Finally, the black sample was taken out after cooling to room temperature, and the heterojunction catalyst was obtained.

[0049] The XRD pattern of the reduction product obtained in this example is shown in Figure 3The results show that the CoMoO4 precursor is completely transformed into Co, CoO and Mo2N. The peaks at 44.2° and 51.5° correspond to the (111) and (200) crystal planes of Co (PDF#15-0806). The peaks at 36.9°, 42.8° and 62.2° are attributed to the (111), (200) and (220) crystal planes of metallic CoO (PDF#70-2855). The peaks at 37.4°, 43.5°, 63.1° and 75.7° match the (111), (200), (220) and (311) crystal planes of Mo2N (PDF#25-1366), respectively.

[0050] The SEM image of the reduction product obtained in this example is shown in Figure 4 (a) The results show that the reduced sample retains the initial morphology of the CoMoO4 microrod array. The further enlarged SEM image in the figure shows that the surface of the microrods is decorated with nanoparticles, which are metal Co.

[0051] The TEM image and element distribution diagram of the reduction product obtained in this example are shown in Figure 5 . Figure 5 It can be seen in a that after thermochemical treatment, the material still maintains a nanorod-like morphology, and the uniformly distributed black areas on the rods may be caused by the contrast of elemental mass after phase separation. The high-resolution transmission electron microscopy (HR-TEM) image (5b) shows different lattice fringes with spacings of 0.204, 0.211, and 0.241 nm, corresponding to the (111), (200), and (111) crystal plane spacings of Co, CoO, and C / Mo2N, respectively. Figure 5 c shows a clear transmission electron microscope image of the nanorod edge, proving that the carbon element in urea is only used as a doping element and has not been transformed into an outer carbon layer. In addition, the element distribution diagram in the figure verifies the uniform distribution of Co, Mo, O, N and C, suggesting the potential carbon doping in Mo2N. Proving the successful synthesis of Co-CoO-C / Mo2N heterojunction.

[0052] The XPS spectrum of the reduction product obtained in this example is shown in Figure 6 The presence of Mo-C in the high-resolution images of Mo 3d and C1s indicates that C has been successfully doped into MoN. These high-resolution images demonstrate the successful preparation of heterogeneous nanorod arrays with rich interfaces composed of metallic Co, CoO and carbon-doped Mo2N.

[0053] Use scissors to cut the product of this example grown on the carbon cloth into 1×1.5 cm 2 The HER electrocatalytic performance of the samples was tested in 1.0 M KOH solution. Figure 7 and Figure 8The LSV curve and Tafel slope in 1.0 M KOH solution are shown in Figure 2. -2 The current density of 100 mA cm-2 shows an ultra-low overpotential of 27 mV. -2 The current density only requires 113mV overpotential. The Tafel slope is 37mV dec -1 , illustrating the rapid reaction kinetics in the catalytic process of this example.

[0054] The above results show that the Co-CoO-C / Mo2N-600 prepared in this example has an electrocatalytic hydrogen evolution performance comparable to that of Pt / C under alkaline conditions and has prospects for practical industrial applications.

[0055] Example 2

[0056] A transition metal multiphase heterojunction catalyst, the preparation method of which is substantially the same as that of Example 1, except that the hydrogen concentration is increased to 10 vol%.

[0057] The phase composition of the reduction product obtained in this example is the same as that in Example 1 ( Figure 3 ), the morphology still maintains the nanorod array ( Figure 4 (b)). The LSV curve of the obtained product Co-CoO-C / Mo2N-500 in 1.0M KOH solution is shown in Figure 7 , up to 10mAcm -2 The current density is only 22mV, and the overpotential is only 22mV. -2 The current density only requires 110 mV overpotential, and the performance is close to that of Example 1.

[0058] Example 3

[0059] A transition metal multiphase heterojunction catalyst, the preparation method of which is substantially the same as that of Example 1, except that the temperature of annealing in argon in step 2) is 700°C.

[0060] The phase composition of the reduction product obtained in this example is the same as that in Example 1 ( Figure 3 ), the morphology still maintains the nanorod array, but the surface becomes rough due to the structural contraction from oxide to nitride and the growth of metal Co ( Figure 4 (c)). The LSV curve of the obtained product Co-CoO-C / Mo2N-700 in 1.0M KOH solution is shown in Figure 7 , up to 10mA cm -2 The current density is only 49mV, and the overpotential is only 49mV. -2 The current density of 195 mV is only required. The results show that the optimal second step annealing temperature is 500-600℃.

[0061] Comparative Example 1

[0062] A transition metal multiphase heterojunction catalyst, the preparation method of which is substantially the same as that of Example 1, except that the heat treatment temperature in step 1) is 400°C.

[0063] The XRD pattern of the product obtained in this comparative example is shown in Fig. 9 , no metallic Co appeared in the reduction product, which indicated that the Co-CoO-C / Mo2N electrocatalytic material could not be obtained under this condition.

[0064] Comparative Example 2

[0065] A transition metal multiphase heterojunction catalyst, the preparation method of which is substantially the same as that of Example 1, except that the 7 vol% H2 / Ar gas in step 1) is replaced with argon gas of the same flow rate.

[0066] The XRD pattern of the product obtained in this comparative example is shown in Fig.10 In addition to Co, CoO and Mo2N, the product also contains a large amount of incompletely reduced Co2Mo3O8. The results show that the Co-CoO-C / Mo2N electrocatalytic material cannot be obtained under this condition.

[0067] Comparative Example 3

[0068] A transition metal multiphase heterojunction catalyst, the preparation method of which is substantially the same as that of Example 1, except that in step 1), only 200 sccm of 7% H2 / Ar is introduced, and no urea is added.

[0069] The XRD pattern of the product obtained in this comparative example is shown in Fig.11 , the reduction products include CoO and Co2Mo3O8. The results show that the Co-CoO-C / Mo2N electrocatalytic material cannot be obtained under this condition.

[0070] Comparative Example 4

[0071] A transition metal multiphase heterojunction catalyst, the preparation method of which is substantially the same as that of Example 1, except that the urea in step 1) is replaced by 30 sccm of NH3 gas.

[0072] The XRD pattern of the product obtained in this comparative example is shown in Fig.12 The product contains Co, CoO and Mo2N. XPS spectrum ( Fig.13 ) shows that the comparative example does not form carbon-doped Mo2N. The results show that the Co-CoO-C / Mo2N electrocatalytic material cannot be obtained under this condition.

[0073] The above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, so the obvious changes or modifications derived are still within the protection scope of the invention.

Claims

1. A method for preparing a transition metal multiphase heterojunction catalyst, characterized in that: The steps include: 1) providing a CoMoO4 precursor loaded on a carbon cloth; 2) Using a carbonitride that is easily decomposed by heat as a reaction source, placing the CoMoO4 precursor supported on the carbon cloth in a reaction atmosphere, performing a heat treatment, and then cooling to room temperature to obtain the transition metal multiphase heterojunction catalyst.

2. The method for preparing a transition metal multiphase heterojunction catalyst according to claim 1, characterized in that: The method further comprises, after step 2), performing a secondary annealing on the product obtained in step 2) in an argon atmosphere.

3. The method for preparing a transition metal multiphase heterojunction catalyst according to claim 2, characterized in that: The secondary annealing temperature is 500-700° C., and the heat preservation time is 1-6 hours.

4. The method for preparing a transition metal multiphase heterojunction catalyst according to claim 1, characterized in that: The carbonitride is one of urea, cyanamide, dicyanamide or melamine.

5. The method for preparing a transition metal multiphase heterojunction catalyst according to claim 1, characterized in that: The reaction atmosphere in step 2) is a mixed atmosphere of hydrogen and argon.

6. The method for preparing a transition metal multiphase heterojunction catalyst according to claim 1, characterized in that: The heat treatment in step 2) is performed at a temperature of 500 to 800° C. for a time of 1 to 6 hours.

7. The method for preparing a transition metal multiphase heterojunction catalyst according to claim 1, characterized in that: The CoMoO4 precursor has the morphology of nanorods.

8. The method for preparing a transition metal multiphase heterojunction catalyst according to claim 1, characterized in that: The CoMoO4 precursor supported on the carbon cloth is prepared by dissolving Na2MoO4·2H2O and Co(NO3)2·6H2O in water, immersing the carbon cloth in water, performing a hydrothermal reaction, and washing the carbon cloth to obtain the CoMoO4 precursor supported on the carbon cloth.

9. The transition metal multiphase heterojunction catalyst obtained according to the preparation method according to any one of claims 1 to 8.

10. Use of the transition metal multiphase heterojunction catalyst according to claim 9 in the field of electrocatalytic hydrogen evolution.

Citation Information

Patent Citations

  • Preparation of efficient Co / NiCoP / CC heterogeneous nanoparticle hydrogen evolution reaction electrocatalyst

    CN115323392A

  • A double heterojunction catalyst for electrocatalytic hydrogen evolution reaction and preparation method thereof

    CN116876017B